Business Competitiveness of Small Medium Enterprise in Pandemic Era Covid-19 (Case Study on Souvenir Business in the Special Economic Area of Tourism Likupang, North Sulawesi Province, Indonesia) - Kawulur, Arie Frits; Mawitjere, Noula; Kawulur, Hisky (Journal of International Conference Proceedings, 2021)
This study aims to describe the small medium enterprises that grow and exist in "Likupang" Tourism Special Economic Zone, North Sulawesi Province, Indonesia, especially for micro and small businesses in the souvenir business sector, focusing on the factors of utilizing appropriate technology, online/offline marketing and human capital. This research uses qualitative design with case study method by digging up in-depth information and data on business environment during the Covid-19 pandemic since 2020 until now. The results show that there are micro and small businesses that use appropriate technology in making souvenirs, the findings are still limited to technology tools for forming souvenir products, another result showed the innovation in product design is still lacking, employees only imitate common things and did not create products typical to Likupang area. In terms of marketing strategies, it was found that the Covid-19 pandemic hit the tourism industry, including souvenir businesses badly. This made souvenir business owners apply marketing strategies by selling products at sites as well as offering products through social media. Another finding from human capital factor, there are still business owners and employees who do not have entrepreneur mindset, even though in terms of product-making skills, they are classified as skilled craftsmen.